Unexpected high levels of iron and rubidium in the peritoneal fluid of endometriosis patients - López-Botella, Andrea; Romero, Alejandro; Sánchez, Raquel; Todolí-Torró, José-Luis; Velasco, Irene; Acién, Maribel; Gómez-Torres, María José (The Science of the total environment, 2025)
Endometriosis disease affects up to 10 % of menstruating people worldwide and can lead to infertility. Environmental pollutants are risk factors influencing the probability of developing endometriosis. We aimed to explore the differences in the content of potentially toxic elements (PTEs), trace, and ultra-trace elements in the peritoneal fluid (PF) of endometriosis subjects compared to control subjects. A hospital-based case–control study was conducted between 2020 and September 2022 at the Obstetrics and Gynecology Service of San Juan University Hospital (Alicante, Spain), where PF samples were collected from 61 patients, including both endometriosis cases and controls. The concentration of barium (Ba), bismuth (Bi), cadmium (Cd), cobalt (Co), lithium (Li), manganese (Mn), nickel (Ni), lead (Pb), rubidium (Rb), tin (Sn), strontium (Sr), titanium (Ti), vanadium (V), chromium (Cr), copper (Cu), iron (Fe), and zinc (Zn) were determined by inductively coupled plasma mass spectrometry. Differences in elemental concentrations between groups were assessed with Kruskal-Wallis test. Binary logistic regression was used to examine the association between elemental concentrations and disease odds. Spearman's Rho (ρ) correlation coefficients and partial correlation networks were employed to assess elemental concentration correlations for each group. We found significantly higher levels of Rb, and Fe, and lower Sr and Li concentrations in the PF of patients with endometriosis. Adjusted odds ratios (aOR) showed that higher Rb concentration was associated with increased odds of endometriosis (aOR = 1.02, 95 % CI: 1.00–1.04), while higher Sr was linked to reduced odds (aOR = 0.93, 95 % CI: 0.88–0.99). Different correlation and association patterns were observed between elemental concentrations in the control and endometriosis groups. Data from this study show different levels of PTEs, trace, and ultra-trace elements in the PF of endometriosis subjects. This suggests environmental exposures and/or pathophysiological and metabolic alterations are associated with the disease. [Display omitted] •Potentially toxic, trace and ultra-trace elements were quantified in peritoneal fluid from patients with endometriosis.•Results showed significantly higher levels of Rb, and Fe, with lower Li and Sr concentrations in endometriosis patients.•Distinct correlation and association patterns were found between element concentrations in control and endometriosis groups.•Differences may reflect disease-related changes from environmental exposure or pathophysiological or metabolic alterations.